The Effect of Oral Carbohydrates on Blood Sugar and Hemodynamic Parameters in Children Undergoing Inguinal Hernia Surgery - T Karami; S Hariri; H Houshyar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Fasting before surgery can cause metabolic stress and insulin resistance. The aim of this study is to investigate the effect of oral carbohydrates before surgery on blood sugar levels and hemodynamic indicators in children under three years of age who are candidates for inguinal hernia surgery. Methods: In this double-blind clinical trial, 207 children under three years of age who were candidates for inguinal hernia surgery were randomly divided into three groups. Patients in the carbohydrate group received 5 cc/kg of 20% dextrose solution orally, in the water group, 5 cc/kg of drinking water 2 hours before surgery, and in the control group, standard fasting was applied before surgery. Mean arterial pressure, heart rate and blood sugar at different times (5, 10, 15 and 20 minutes) as well as the incidence of vomiting were compared between the three groups. Findings: Heart rate changes were significantly different between the three groups (p=0.002). The mean changes in heart rate at 10, 15 and 20 minutes were -6.76±0.89, -10.9±1.25 and -12.47±1.3 in the oral carbohydrate group, -4.03±0.65, -7.4±0.75 and -8.76±0.8 in water group and -2.7±0.36, -5.9±0.72 and -6.9±0.73 in the control group, respectively. In the oral carbohydrate group, the mean blood sugar changes during surgery (+4.15±4.8 and p=0.39) and during recovery (-0.35±0.94 and p=0.94) were not significant. The mean changes in blood sugar during surgery (+35.01±1.8) and during recovery (+46.57±1.4) in the water group, as well as blood sugar increase during surgery (42.12±1.5) and recovery (+39±1.3) in the control group compared to before induction of anesthesia were statistically significant (p<0.001). Conclusion: The results of the study showed that preoperative oral carbohydrate intake provides more stable hemodynamics in children undergoing inguinal hernia surgery. Despite the high blood sugar in the oral carbohydrate group before induction of anesthesia, its changes during surgery and recovery are small compared to the water and control groups.